PHYSICS IN MICRO HYDRO POWER PLANT IN CIKADU RIVER MEKAR MULYA VILLAGE, SITURAJA DISTRICT, SUMEDANG REGENCY, WEST JAVA - (NIM : 90215304), NUROHMAN
Indonesia has a tropical climate with high rainfall, this means that regions in Indonesia store abundant renewable energy sources, because water is a natural resource that can be renewed through a process called the hydrologic cycle. Micro Hydro Power Plants are energy conversion processes the potential energy of water becomes mechanical energy by a turbine and then becomes electrical energy by a generator on a small scale with an output power of less than 100 kWH. The planning of this Micro Hydro Power Plant starts from a literature study relating to the manufacture of Hydroelectric Power Plants. Then conducted a survey to the location of the Cikadu river located in Mekarmulya village, Situraja district, Sumedang district. After obtaining water debit and estimated water fall (head) then survey to CV. Cihanjuang Inti Teknik located on Jl. Cihanjuang Cimahi as a producer of Micro Hydro to Mini Hydro Turbines to discuss turbines that are suitable with the conditions of the place to be built by the MHP. The second survey to the location to measure and then make a civil construction plan in the form of dams , intake size and material, penstock, tranquilizing pond and power house. Dam or dam utilizes irrigation dams with the aim of simplifying and saving costs. The water discharge based on temporary measurements is 45 liters / second, while the height of falling water is 3 meters. Based on the data I obtained, the turbine that is suitable for the location there is the Open Flume 125 propeller turbine and the resulting power is 1,058 Watts which are distributed to 10 houses.